Postprandial Hyperlipidemia: Association with Inflammation and Subclinical Atherosclerosis in Patients with Rheumatoid Arthritis - Mena-Vázquez, Natalia; Redondo-Rodríguez, Rocío; Rioja Villodres, José; Jimenez-Nuñez, Francisco Gabriel; Manrique-Arija, Sara; Lisbona-Montañez, José Manuel; Cano-García, Laura; Rojas Gimenez, Marta; Ureña, Inmaculada; Valdivielso-Felices, Pedro; Fernández-Nebro, Antonio (IOAP-MDPI, 2022)
Objective: To describe postprandial lipidemia in patients with rheumatoid arthritis (RA) and to analyze its association with subclinical atherosclerosis and inflammatory activity. Methods: Observational study of 80 cases of RA and 80 sex- and age-matched controls. We excluded individuals with dyslipidemia. Postprandial hyperlipidemia (PPHL) was defined as postprandial triglycerides >220 mg/dL and/or postprandial ApoB48 levels >75th percentile (>p75). Plasma lipids, cholesterol, triglycerides, ApoB48, and total ApoB were evaluated at baseline and after a meal. Other variables analyzed included subclinical atherosclerosis (defined as presence of carotid atheromatous plaque), inflammatory activity (disease activity score (DAS28-ESR)), cytokines, apolipoproteins, and physical activity. A multivariate analysis was performed to identify factors associated with PPHL in patients with RA. Results: A total of 75 patients with RA and 67 healthy controls fulfilled the inclusion criteria. PPHL was more frequent in patients with RA than controls (No. (%), 29 (38.70) vs. 15 (22.40); p = 0.036), as was subclinical atherosclerosis (No. (%), 22 (30.10) vs. 10 (14.90); p = 0.032). PPHL in patients with RA was associated with subclinical atherosclerosis (OR (95% CI) 4.69 (1.09–12.11); p = 0.037), TNF-α (OR (95% CI) 2.00 (1.00–3.98); p = 0.048), high-sensitivity C-reactive protein (OR (95% CI) 1.10 (1.01–1.19); p = 0.027), and baseline triglycerides (OR (95% CI) 1.02 (1.00–1.04); p = 0.049). Conclusion: PPHL was more frequent in patients with RA than in controls. PPHL in patients with RA was associated with inflammation and subclinical atherosclerosis.
Keywords: Artritis reumatoide; Rheumatoid arthritis; Postprandial lipemia; Triglycerides; Apolipoprotein B48; Inflammation; Subclinical atherosclerosis